THE RELATIONSHIP BETWEEN THE STUDENTS’ INTEREST IN LEARNING ENGLISH AND THEIR ACADEMIC ACHIEVEMENT IN SMP BRAWIJAYA SMART SCHOOL - LUNGIT, DHAMASTUTI DIAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Interest, Individual Interest, Academic Achievement.The students’ interest is an important thing in educational system, because interest helps students to grab their goal. Students who have good interest inEnglish will do their best to get their goal. This present study explored two problems: (1) How is the SMP Brawijaya Smart School students’ interest in learning English ? (2) How is the relationship between student interest in learning English with their academic achievement.This study use SIQ questionnaire as the instrument to find out thestudents’ interest in learning English which contained of 18 questions. For analysing thedata, this study uses SPSS program (ANOVA and Pearson correlation). This study uses quantitative research since the writer tried to calculate the questionnaire. Thedata of this study were the SIQ questionnaire which is filled by eight grade students at SMP Brawijaya Smart School.By analysing 88 questionnaires which are filled by eight grade students of SMP BSS , the writer revealed the following finding: (1) there are many studentsthat have good enough interest in learning English, (2) there is relationshipbetween students’ interest in learning English with their academic achievement, (3) environment gives great influence to students’ interest in learning.Finally, the writer suggests the next researchers to investigate the factors which influence students’ interest in learning English. The future researchers can also use other objects for their studies.